Semantic features of phrases with interrogative pronouns - Islomova Shahnoza (Genius Journals, 2022)
The rhyming feature clears our speech of unnecessary repetitions and provides a concise statement of thought. This group of words is not only independent words, but also imitations, pronouns, phrases, sentences and even the ability to replace and point to the text. Interrogative pronouns and forms derived from them are involved in the formation of phrasal verbs. does not represent the nose at all.
Keywords: phrase; definite; feature